Democratic security and integration in the Andean countries. Consolidation or fragmentation? - Pinto, María Elena (2016)
Since the late 1980s, the members of the Andean Pact decided to reorganize their regional institutions, and strengthen their process of integration. Observing the Andean region from a Venezuelan perspective, this article considers the centrifugal and centripetal forces explaining the complex relationship among the internal conflict of each Andean country, its individual security, the problem of collective security, and the process of integration. Finally, the author advances some proposals directed to overcome the obstacles currently confronting Andean integration.